Kemampuan Pemahaman Konsep Matematis Siswa Kelas VII pada Materi Himpunan - Nuriah, Sinta; Aripin, Usman; Rohaeti, Euis Eti (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
This research is motivated by the low ability to understand mathematical concepts of students. The purpose of this study is to analyze the ability to understand mathematical concepts on the set material. This study uses a qualitative descriptive method. The subjects of this study were 29 students of class VII-G MTs AL-Mukhtariyah Mande. Data collection techniques using written test techniques. Then the data obtained were analyzed using descriptive statistics, namely mean (average) and percentage. The results showed there were 20.7% of students in the high category, 41.4% of students in the medium category, and 37.9% of students in the low category. Based on the results of the study, the researchers concluded that the ability to understand mathematical concepts of students in Class VII-G MTs Al-Mukhtariyah Mande is in the medium category.